PSVIII-2 Antibody yield for polyclonal egg yolk antibody (IgY) production in laying hens. (30th November 2020) - Nolden, Cherrie; Grisham, Abbey; Schaefer, Dan; Akins, Matt; Cook, Mark
Abstract: Antibody production in egg yolks of immunized laying hens is an alternative to conventional mammalian production. Antibody yield peak and duration have not been described for immunoglobulin Y technology using Freund's incomplete adjuvant (FIA) and C-phosphate-guanosine oligodeoxynucleotides (CpG-ODN) without the inclusion of Freund's complete adjuvant for enhancing the immune response to an interleukin-10 (IL-10) peptide. This study sought to describe the antibody titer production for an 8 amino acid sequence from the surface of the bovine IL-10 protein (VMPQAENG) as the antigen emulsified with CpG-ODN and FIA in phosphate buffered saline (PBS). 60 hens were assigned to receive the complete vaccine (Peptide), 20 received the vaccine without the IL-10 peptide (Control), and 8 received a PBS injection (Blank). Hens were immunized with 0.25 mL in 4 locations, each breast and each thigh on days 1, 15 and 29. The complete vaccine delivered 0.6 mg IL-10 peptide, 8 µg CpG-ODN, and 0.33 mL FIA per hen on each vaccination day. Eggs were collected regularly until 175 days after the first immunization and the anti IL-10 peptide activities of the yolk were determined by ELISA. Egg titers by treatment were analyzed with a repeated measures ANOVA in SAS. The supplementation of FIA with CpG-ODN produced high titers, of over 100 µg of antibody per mL of yolk (µg Ab/mL yolk), around day 33 through day 76, with a slow decline through day 175 when average titers remained above 40 µg Ab/mL yolk. Peptide egg titers were significantly higher than Blank or Control titers from day 31 though day 175 (P < 0.0001). Titers recovered from Marcq et al. (2015) with similar methods were 1.5 to 7 times lower than these results over the same number of days.